Pakistan in the twentieth century : a political history - Ziring, Lawrence ([S.l.] : Oxford University Press, 2000)
This book by a leading scholar is the definitive history of Pakistan. Beginning with an examination of the people and forces that shaped the construction of an independent, predominantly Muslim state within the subcontinent, Ziring provides an incisive and comprehensive description of the events that influenced Pakistan's development in the subsequent fifty years.